ENERGY CONSUMPTION, TRADE OPENNESS AND GROWTH NEXUS IN TURKEY: EVIDENCE FROM VECM - Elma Satrovic (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Thisresearch investigates the relationship between energy consumption (ENE), tradeopenness (TI) and economic growth (GDP) in the case of Turkey in the period1970-2015. VECM is employed. The results suggest along-run causality which is inferred from the statistically significant errorterm with GDP and ENE. However, short-run coefficients are not found to besignificant in the case of GDP and TI equation. Moreover, the findings suggestthat a percentage change in ENE will result in a 1.35% increase in real GDP percapita. While for TI, a percentage change in this variable will result in 0.13%decrease in GDP in the long-run. Hence, real GDP per capita is elastic to thechange in energy consumption but inelastic to the change in TI. This papersummarizes in detail the policy implications and the recommendations for futureresearch. At last, the diagnostic tests advocate the stability of the model.